BRANDY EQUITY E O DESENVOLVIMENTO SUSTENTÁVEL: O CASO COCA COLA - Lima, André de Oliveira (2013)
This project s goal is to demonstrate how companies have been using sustainability as a source of competitive advantage in recent years and if it has become a source of differentiation to customers. This study aims to verify if brands that do have sustainability as a value and that can demonstrate this value through concrete actions have been preferred by customers. This projected developed an exploratory study of Coca-Cola Company in order to verify if sustainability is among the key purchasing criteria for customers in Brazil. The results of this project show that Brazilian consumers are not aware of sustainable actions developed by companies. Price is the main purchasing criteria used by customers in Brazil. However, within younger generations sustainability appears as a key concern and value, which suggests that it can become a decision driver in future years.